James and the giant peach [videorecording (DVD)] - Dahl, Roald; Selick, Henry (Disney DVD : distributed by Buena Vista Home Entertainment, 1996)
A wildly imaginative tale about a little boy who journeys to a wondrous city "where dreams come true".